Education and neoliberalism in Peru in the '90s - Pacheco Lay, Gonzalo (1993)
The times change. From the steam engine in the first years of the beginning of the industrial revolution we passed, at the end of the 20th century, to automated production controlled by computers. The automation of the industrial process has allowed robots to displace human labor. Notwithstanding this displacement of the human factor, the labor market is transformed and new specialties arise in it.